2020
DOI: 10.1002/adfm.202000550
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Temperature‐Dependent Charge Extraction and Trapping in Perovskite Solar Cells

Abstract: Understanding the factors that limit the performance of perovskite solar cells (PSCs) can be enriched by detailed temperature (T)-dependent studies. Based on p-i-n type PSCs with prototype methylammonium lead triiodide (MAPbI 3 ) perovskite absorbers, T-dependent photovoltaic properties are explored and negative T-coefficients for the three device parameters (V OC , J SC , and FF) are observed within a wide low T-range, leading to a maximum power conversion efficiency (PCE) of 21.4% with an impressive fill fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 51 publications
(94 reference statements)
2
41
0
Order By: Relevance
“…Taskensen et al also witnessed the simultaneous improvement of V OC and fill factor (FF) on CZTSe solar cells during cooling to 240 K [ 163 ]. As illustrated in Figure 7 b, both the FF and PCE of hybrid perovskite solar cells significantly increase with declining temperature [ 164 ]. Temperature-dependent photovoltaic properties are closely related to light absorption, the motion of photogenerated carriers and even the structure and composition of devices.…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
See 4 more Smart Citations
“…Taskensen et al also witnessed the simultaneous improvement of V OC and fill factor (FF) on CZTSe solar cells during cooling to 240 K [ 163 ]. As illustrated in Figure 7 b, both the FF and PCE of hybrid perovskite solar cells significantly increase with declining temperature [ 164 ]. Temperature-dependent photovoltaic properties are closely related to light absorption, the motion of photogenerated carriers and even the structure and composition of devices.…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
“…Chen et al studied cooling-caused variations in MAPbBr 3 solar cells and proposed the insulating nature of a charge-extraction layer, rather than an absorption layer restricting performance at low temperature [ 174 ]. Represented by Figure 7 e, the PL intensity of the charge-transporting layer is lowered compared to control samples at various temperatures, implying a more efficient charge transfer in interfaces, especially at low temperature [ 164 ]. Nevertheless, Shao et al observed that deteriorated charge-carrier extraction caused a PCE drop at low temperature when using [ 60 ] PCBM as an electron extraction layer [ 103 ].…”
Section: Low-temperature Enhancement In Photoelectric Performancementioning
confidence: 99%
See 3 more Smart Citations